The Synthesis of Nucleoside 2′, 3′‐Cyclic Monophosphate Analogs with Regio‐ and Stereospecificity. Issue 11 (26th November 2021) - Nassir, Molhm; Saady, Abed; Cohen, Natalie Pariene; Fischer, Bilha
Abstract: This article presents a new method for the rapid, stereoselective and regioselective synthesis of nucleoside 2′, 3′‐ O, O ‐phosphorothioate and 2′, 3′‐ O, O ‐phosphoroselenoate molecules. The method avoids the use of protection groups, chiral reagents, and chiral metal catalysts, as well as complicated chiral separations. This synthetic method has been applied successfully to all of the natural nucleosides. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of 2‐chloro‐1, 3, 2‐dithiophospholane (6 ) Basic Protocol 2 : Preparation of 2‐cyanoethoxy‐thio‐dithiophospholane (8 ) Basic Protocol 3 : Preparation of 2‐cyanoethoxy‐seleno‐dithiophospholane (9 ) Basic Protocol 4 : Preparation of uridine‐2′, 3′‐ O, O ‐phosphorothioate ( S p, exo; 1A ) Basic Protocol 5 : Preparation of uridine‐2′, 3′‐ O, O ‐phosphoroselenoate ( S p, exo; 11 ) Basic Protocol 6 : Preparation of adenosine‐2′, 3′‐ O, O ‐phosphorothioate ( S p, exo; 12 ) Basic Protocol 7 : Preparation of thymidine‐2′, 3′‐ O, O ‐phosphorothioate ( S p, exo; 13 ) Basic Protocol 8 : Preparation of cytosine‐2′, 3′‐ O, O ‐phosphorothioate ( S p, exo; 14 ) Basic Protocol 9 : Preparation of guanosine‐2′, 3′‐ O, O ‐phosphorothioate ( S p, exo; 15 )